Harnessing TikTok for learning: Examining its impact on students' mathematical numeracy skills - Wahyuni, Nur; Alam, Sri Rahayu; Alghiffari, Eka Kevin; Siswanto, Deny Hadi (Universitas Ahmad Dahlan, 2024)
Mathematical numeracy is a fundamental skill that students need to develop. Social media platforms like TikTok have the potential to support students in enhancing their mathematical numeracy skills. This study examines the effect of using TikTok on students' mathematical numeracy skills through a quantitative approach with a pre-experimental design. The research sample consisted of 30 class XI science students from Senior High School of Muhammadiyah Mlati, Yogyakarta, selected using a nonprobability sampling technique. The learning process integrated TikTok as a supplementary learning medium, and learning outcomes were assessed using pretests and posttests with validated instruments. Data collection involved a questionnaire (10 items) regarding learning experiences with TikTok and a numeracy test (5 items). Simple linear regression analysis, conducted with SPSS-25, confirmed normal data distribution and a linear relationship between TikTok use and numeracy skills. The regression analysis yielded a significance value of 0.015 (<0.05), indicating a significant effect of TikTok on students’ mathematical numeracy skills. The R Square value of 0.195 suggests that TikTok accounts for 19.5% of the improvement in numeracy skills, with the remaining 80.5% attributed to other factors. The n-Gain test result of 0.63 classifies the numeracy skill enhancement as moderate. These findings highlight TikTok’s effectiveness as an alternative learning medium for improving mathematical numeracy skills. This study implies that TikTok can be integrated into the teaching process as a supplementary tool to effectively enhance students’ mathematical numeracy skills.